2008
DOI: 10.1186/1476-069x-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Complaints of the arm, neck and shoulder among computer office workers in Sudan: a prevalence study with validation of an Arabic risk factors questionnaire

Abstract: Background: Complaints of the arm, neck and/or shoulders (CANS) in general and computer-related disorders in particular affect millions of computer office workers in Western developed countries. However, with the widespread use of computer systems in developing countries, the associated musculoskeletal complaints are yet to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
7
36
0
8
Order By: Relevance
“…MUEQ is a 95-item questionnaire about the potential risk factors for WRMSDs of the upper extremities, containing the following aspects: work station, posture during work, quality of break time, job demands, job control, social support, quality of the work environment and presence of complaints of the upper extremities 17. The questions have to be answered on a 5-point Likert scale, where 1 reflects ‘always’ and 5 reflects ‘never’.…”
Section: Methodsmentioning
confidence: 99%
“…MUEQ is a 95-item questionnaire about the potential risk factors for WRMSDs of the upper extremities, containing the following aspects: work station, posture during work, quality of break time, job demands, job control, social support, quality of the work environment and presence of complaints of the upper extremities 17. The questions have to be answered on a 5-point Likert scale, where 1 reflects ‘always’ and 5 reflects ‘never’.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the highest incidences were found for neck and shoulder symptoms (64% and 41%, respectively). 8 Although previous studies found that the prevalence of the musculoskeletal symptoms for visual display terminal users was high, the prevalence among high workload computer users has not been investigated.…”
mentioning
confidence: 99%
“…Katılımcıların %68,2'si kadın (73) Bilgisayar ile çalışanlarda yapılmış çalışmalarda en sık yakınma bulunan bölge boyun bölgesi olup çalışmamızla benzerlik göstermektedir. 6,8,15 Çalışmamızda kişilerin yaşları arttıkça omuz ve el-el bileği bölgelerinde KİS yakınmalarının da artmakta olduğu tespit edildi. Yapılmış çalışmalarda yaşın KİS yakınması için bir risk faktörü olarak incelendiği çalışmalar kısıtlı olup, çalışmamızla benzer sonuçlara ulaşan çalışmalar bulunmaktadır.…”
Section: Bulgularunclassified
“…4 Kesitsel çalışmalarda bilgisayarla çalışanlarda yıllık boyun ve üst ekstremite yakınması prevalansı %10-86 arasında bulunmuştur. [5][6][7][8] Mesleksel kas iskelet sistemi hastalıkları için risk faktörleri fi ziksel ve ergonomik, psikososyal ve kişisel risk faktörleri olmak üzere üçe ayrılabilir. Fiziksel ve ergonomik risk faktörleri arasında tekrarlayıcı hareketler, uzun süreli aynı pozisyonda çalışmak, kişiye uyumsuz masa ve sandalye özellikleri gibi faktörler yer almaktadır.…”
Section: Introductionunclassified